DESAIN APLIKASI WEB MINIPIANO: PENGENALAN TANGGA NADA PADA ANAK DI ERA PEMBELAJARAN DIGITAL - Dhea Elvionita Surya; Tri Karyono; Ayo Sunaryo; Salomo Julio Elsada Lautt (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to design and develop the MiniPiano web application as an interactive learning medium to introduce the concept of musical scales to children aged 6–11 years. The background of this study stems from the low interest and understanding of children in basic music theory due to learning methods that are still predominantly conventional, verbal, and lack visual and audio stimulation. The method used is Research and Development (R&D) with the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The application was developed through a prototype design process using Figma and code implementation using Visual Studio Code with the integration of multimedia elements in the form of text, images, animations, and audio. The results of the study show that MiniPiano has excellent feasibility based on the assessments of media and material experts, as well as generating positive responses from limited trials with children. This application has been proven to help children understand basic note sequences, increase their interest in learning music, and create an enjoyable learning experience. This study confirms that the use of web-based media and interactive multimedia has the potential to enrich basic music learning and can be an alternative solution in music education for elementary school children.